EPIDEMIOLOGICAL DETERMINANTS OF DENGUE HEMORRHAGIC FEVER (DHF): A LITERATURE REVIEW - Rost, Esther Kendek; Tosepu, Ramadhan (Preventif Journal, 2024)
ABSTRACT Dengue hemorrhagic fever (DHF) is a disease caused by the dengue virus through the bite of the Aedes mosquito, especially Aedes aegypti . Dengue fever is the fastest growing mosquito-borne disease in the world. Tropical and sub-tropical climate countries are at high risk of transmission of the virus. The aim of this paper is to provide an overview of the epidemiological determinants of dengue hemorrhagic fever (DHF) in Indonesia. The method used in this research is a literature review using a comprehensive strategy by collecting articles through searches in several databases, namely Google Scholar, using the following keywords: "online media" and "Epidemiology". The data analysis technique used is descriptive analysis where the research results from the articles found will be explained one by one.. Research results show that the majority of dengue fever cases occur in the 5–14 year age group. The age group 12 years. This is because this age group has a lower immune system compared to older age groups and most of their daily activities are carried out at school, thereby increasing the risk of being bitten by a mosquito that transmits dengue fever due to the nature of the Aedes aegypti mosquito sucking the blood of more than one person. The advice I can give in this research is that we should be able to prevent dengue fever as early as possible by always cleaning the surrounding environment. Keywords: Epidemiology, Dengue Hemorrhagic Fever.